Which Theoretical School is Best? It Depends on How one Frames the Question - W. С. Wohlforth (Международная аналитика)
William C. Wohlforth is a distinguished American political scientist, serving as a faculty member in the Government Department at Dartmouth College since 2000. He holds a degree in international relations from Beloit College and has experience working as a legislative aide in the U.S. House of Representatives. Dr. Wohlforth completed his graduate studies at Yale University, where he earned both an M.A. in international relations and a Ph.D. in political science. He has previously held academic positions at Princeton University and Georgetown University. Dr. Wohlforth’s scholarly expertise encompasses international security and foreign policy. His most recent publications include America Abroad: The United States’ Global Role in the 21st Century (Oxford University Press, 2018), co-authored with Stephen G. Brooks, and the forthcoming A Measure Short of War: A Brief History of Great Power Subversion (Oxford University Press, December 2024), co-authored with Jill Kastner.